Chromatic Multifocal Pupillometer for Objective Perimetry and Diagnosis of Patients with Retinitis Pigmentosa - Chibel, Ron; Sher, Ifat; Ben Ner, Daniel; Mhajna, Mohamad O; Achiron, Asaf; Hajyahia, Soad; Skaat, Alon; Berchenko, Yakir; Oberman, Bernice; Kalter-Leibovici, Ofra; Freedman, Laurence; Rotenstreich, Ygal (Ophthalmology (Rochester, Minn.), 2016)
To assess visual field (VF) defects and retinal function objectively in healthy participants and patients with retinitis pigmentosa (RP) using a chromatic multifocal pupillometer. Cross-sectional study. The right eyes of 16 healthy participants and 13 RP patients. Pupil responses to red and blue light (peak, 485 and 625 nm, respectively) presented by 76 light-emitting diodes, 1.8-mm spot size at different locations of a 16.2° VF were recorded. Subjective VFs of RP patients were determined using chromatic dark-adapted Goldmann VFs (CDA-GVFs). Six healthy participants underwent 2 pupillometer examinations to determine test-retest reliability. Three parameters of pupil contraction were determined automatically: percentage of change of pupil size (PPC), maximum contraction velocity (MCV; in pixels per second), and latency of MCV (LMCV; in seconds). The fraction of functional VF was determined by CDA-GVF. In healthy participants, higher PPC and MCV were measured in response to blue compared with red light. The LMCV in response to blue light was relatively constant throughout the VF. Healthy participants demonstrated higher PPC and MCV and shorter LMCV in central compared with peripheral test points in response to red light. Test-retest correlation coefficients were 0.7 for PPC and 0.5 for MCV. In RP patients, test point in which the PPC and MCV were lower than 4 standard errors from the mean of healthy participants correlated with areas that were indicated as nonseeing by CDA-GVF. The mean absolute deviation in LMCV parameter in response to the red light between different test point was significantly higher in RP patients (range, 0.16-0.47) than in healthy participants (range, 0.02-0.16; P < 0.0001) and indicated its usefulness as a diagnostic tool with high sensitivity and specificity (area under the receiver operating characteristic curve (AUC), 0.97, Mann-Whitney-Wilcoxon analysis). Randomly reducing the number of test points to a total of 15 points did not significantly reduce the AUC in RP diagnosis based on this parameter. This study demonstrates the feasibility of using a chromatic multifocal pupillometer for objective diagnosis of RP and assessment of VF defects.